Przekształcenia organizacyjno-prawne i własnościowe w gospodarce komunalnej z perspektywy doświadczeń programu prywatyzacji podmiotów komunalnych PHARE - Żuk, Krzysztof (The Transformation of the Public Utility Sector in Perspective the Municipal Enterprises Privatisation Support Programme of PHARE, 2006)
Local governments in starting transformation in the public utility sector, had no clear and consistent policy for the emerging markets and privatisation of public services. Local governments could not distinguish the most important goal - models of efficient management of public services in the market economy. In the targeted sample, there was a progressive process of "self-learning". However, local governments still need support which should be provided in the form of continuous education, promotion of good practice and technical assistance. The Ministry of the Treasury began conceptual work concerning, with the participation of the EU PHARE assistance fund, two programmes supporting the ownership transformation process in the public utility sector. The Municipal Enterprises Privatisation Support Programmes has been implemented by the Ministry of the Treasury since 1998 under the framework of PHARE 1996 and PHARE 2000 allocation. Funds at the MT's disposal enabled to launch trenches of the programmes for the total of 90 (in the years between 1998 and 2000) and 150 (in the years between 2003 and 2004) participating municipal enterprises. The objective of the programme is to support privatisation and restructuring in municipal entities. Under the framework of this programme technical and training assistance is provided to municipal entities and their founding bodies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 670-680